Income situation of agricultural households in Slovenia after EU accession - Kožar, Maja (Acta agriculturae Slovenica, 2005)
Paper investigates income effects of different direct payments policy options after the accession of Slovenia to the EU by application of a static deterministic total income model for rural households in Slovenia (TIM). Modelis based on actual income data of 120 agricultural households in Slovenia. With respect to the baseline situation before the accession and accession agreement, income situation of analyzed households is likely to improve under all analyzed policy scenarios. The estimated benefits are highest in case of the standard direct payments scheme, followed by basic flat-rate area payment option (entirely decoupled). Model results reveal also that 2003 policy reform will have redistributive impacts in favour of agricultural households engaged in extensive agricultural production.
Keywords: kmečko gospodarstvo; EU; Slovenia; Slovenija; kmetijska politika; reforme; skupni dohodek; neposredna plačila; dohodkovni učinki